2013
DOI: 10.1155/2013/703940
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of PE/Clay Nanocomposites

Abstract: Polyethylene/nanoclay specimens containing from 0 to 5% nanoclays were prepared from a commercially available premixed PE/nanoclay masterbatch containing 50% wt of nanoclay. The masterbatch was diluted to the desired concentration by adding PE along with various amounts of compatibilizer in order to achieve the best possible dispersion of the nanoclay platelets. The dielectric response of the compounded samples was investigated using a combination of time and frequency-domain spectroscopy in order to cover a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Moreover, the comparison between isotropic and oriented morphologies of this nanocomposite revealed that the maximum increase of breakdown strength was equal to 45% and corresponded to the nanocomposite featuring oriented morphology, with both clay platelets and PS domains simultaneously aligned perpendicularly to the applied electric field . This effect is in agreement with findings from the literature reporting that the addition of nanoclays to insulating polymer matrices increases their dielectric breakdown strength and their alignment perpendicular to the applied electric field improves further the results by increasing the tortuosity of the paths taken by the charge carriers . However, the dielectric strength of oriented unfilled SEBS matrix was reduced, compared to isotropic unfilled SEBS, which unfortunately neutralizes the increase observed by the alignment of clay.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the comparison between isotropic and oriented morphologies of this nanocomposite revealed that the maximum increase of breakdown strength was equal to 45% and corresponded to the nanocomposite featuring oriented morphology, with both clay platelets and PS domains simultaneously aligned perpendicularly to the applied electric field . This effect is in agreement with findings from the literature reporting that the addition of nanoclays to insulating polymer matrices increases their dielectric breakdown strength and their alignment perpendicular to the applied electric field improves further the results by increasing the tortuosity of the paths taken by the charge carriers . However, the dielectric strength of oriented unfilled SEBS matrix was reduced, compared to isotropic unfilled SEBS, which unfortunately neutralizes the increase observed by the alignment of clay.…”
Section: Introductionsupporting
confidence: 89%
“…The beneficial effect of clay particles on high electric field properties of insulating polymers such as resistance to electrical treeing, breakdown strength and space charge distribution has been widely reported in the literature. It is attributed to the fact that clay particles, due to their high surface area and layered structure, induce deep‐level trapping sites that reduce the flow of charge carriers and space charge accumulation in the bulk of the insulating polymer matrix as well as inhibit the initiation and growth of electrical trees resulting in higher breakdown strength . Besides, an optimum clay loading at which the maximum enhancement of the breakdown strength of the matrix occurs was often observed .…”
Section: Resultsmentioning
confidence: 99%
“…Investigations also have been extended on the life expectancy and aging of the polymeric housings which are influenced by many factors such as electric stress and its distribution, moisture ingress, oxidation, biological attacks, presence of contaminations, mechanical and thermal stresses, and so on . Other research works regarding the housing materials such as how different material additives like fillers and nanofillers influence the performance of the insulators are also intensively conducted .…”
Section: Historical Development Of Polymeric Insulators For High Voltmentioning
confidence: 99%
“…The effect of nanoparticles on the electrical properties of dielectric materials, in particular, on their ability to record the initiation voltage of partial discharges and to slow the propagation of electrical discharges, trees in polymers and streamers in liquids, leading to breakdown is the subject of many studies around the world for the past 20 years. It appears from the results reported in the literature that some polymers' nano-composites are promising materials for high voltage applications [1][2][3][4][5][6]. The fact that nano-materials present interesting dielectric characteristics results from the large volume fraction of interfaces in the bulk of the material and the ensuing interactions between the surface of the charged nanomaterial and the molecular structure of the hosting material.…”
Section: Introductionmentioning
confidence: 99%